Partition of British India and its influence on literature 1946-1953 - Akram, Lubna (2019)
The partition between India and Pakistan in 1947 brought much misery to the people and greatly affected the literary work of both countries. The impact of the partition between the country has become a significant theme for writers, especially about the peoples’ trauma. This study uncovered the suffering of the Muhajir people in Pakistan through the scholarly literature produced during 1946-1953. It also focuses on the factors that led to the partition of India and Pakistan, the spread of nationalism and social realism in the literary works in India. Also, attentive on the approaches and themes of the partition literature and the impact of the process. History research methods with a triangulation approach applied in this study. Three main elements used were library research, fieldwork and interviews. The library research method involved content analysis of the partition literacy in Pakistan. Primary sources were obtained from the British National Archives, United Kingdom, Islamabad and Lahore. 63 interviews conducted with informants who were witnesses to the partition events. Observations were made on the Muhajir community who were directly involved in the partition event. The findings show that the scholarly works of literature focused on intellectual, social, psychological, cognitive, emotional and ethical themes. Murder and abduction were the main themes among the authors of the partition literature. The study reveals the suffering of the victims during the partition. It also shows the real life of the Muhajir group before, during and after the partition of India and Pakistan. This research proves that the Muhajir people separated from their home due to the partition of India and Pakistan and the importance of power. It has changed the life history of the Indians and the Pakistanis, especially the Muhajir which reflected in the works of the partition studied.